Mathematics Knowledge in Numbering Activities in the Takpala Indigenous Village Community - Andrian Runtius Lalang; I Nengah Parta; Sisworo Sisworo (Jurnal Pendidikan Sains, 2021)
Abstract: The counting activity carried out by the Takpala Indigenous Village community is their way of representing the quantity of a set of goods, counting days, and other activities related to counting in daily activities. Activities are carried out through the use of the Abui language and sticks. The purpose of this study was to describe the mathematical knowledge contained in counting activities by the Takpala Indigenous Village community. This research is ethnographic research with the idea that in each region there is different knowledge based on the needs of the community. Based on the result of the study, it was found that in the use of Abui language there was mathematical knowledge in the form of base 5 and base 10 sub base 5; and in the use of sticks, there are base 10, multiplication 10, and number operation with the concept of place values.Abstrak: Kegiatan membilang yang dilakukan masyarakat Kampung Adat Takpala merupakan cara mereka merepresentasikan jumlah kuantitas sekumpulan barang, menghitung hari dan kegiatan lainnya yang berhubungan dengan menghitung pada aktivitas keseharian. Kegiatan dilakukan lewat penggunaan bahasa Abui dan lidi. Tujuan dari penelitian ini adalah untuk mendeskripsikan pengetahuan matematika yang terdapat dalam kegiatan membilang oleh masyarakat Kampung Adat Takpala. Penelitian ini merupakan penelitian etnografi dengan pemikiran bahwa disetiap daerah terdapat pengetahuan yang berbeda berdasarkan kebutuhan masyarakat. Berdasarkan hasil penelitian diperoleh bahwa pada penggunaan bahasa Abui terdapat pengetahuan matematika berupa bilangan basis 5 dan basis 10 sub basis 5; dan pada penggunaan lidi terdapat bilangan basis 10, perkalian 10 dan operasi bilangan dengan memperhatikan nilai tempat.